HEAVY MINERALS IN PLACER DEPOSIT IN SINGKAWANG WATERS, WEST Kalimantan, RELATED TO FELSIC SOURCE ROCK OF ITS COASTAL AREA - Deny Setiady; Noor C.D. Aryanto (BULLETIN OF THE MARINE GEOLOGY, 2010)
Placer deposits are physically accumulated by fluvial and marine processes in coastal area. Thirty six samples were selected from seventy seven samples of seafloor sediment of Singkawang waters. Those samples have been analyzed microscopically for heavy mineral contents. Based on this analysis, the heavy minerals can be divided into four groups: oxyde and hydroxyde, silicate, sulphide, and carbonate. The source of most heavy minerals in the study area is commonly formed by Felsic igneous rock and finally deposited on the seafloor sediments. Keywords: heavy minerals, placer deposit, felsic igneous rock, Singkawang Endapan letakan secara fisik umumnya terakumulasi oleh proses sungai dan laut. Sebanyak 36 contoh dipilih dari 77 contoh sedimen permukaan dasar laut di Perairan Singkawang. Contoh tersebut telah dilakukan analisis kandungan mineral berat secara mikroskopis. Berdasarkan hasil analisis mineral berat ini dapat dibedakan menjadi empat kelompok yaitu oksida dan hidroksida, silikat, sulfida, dan karbonat. Sebagian besar sumber mineral berat di daerah penelitian pada umumnya berasal dari batuan beku felsik yang akhirnya diendapkan di permukaan dasar laut. Kata kunci: mineral berat, endapan letakan, batuan beku felsik, Singkawang.